Unemployment from the perspective of Islamic economics: A case study among university's graduates in the municipality of Tragan, Libya / Hasan Saeid Mohammed Shukrah - Hasan Saeid , Mohammed Shukrah (2023)
The purpose of the study was to examine the issue of unemployment among university graduates in Tragan, Libya from an Islamic economic perspective. The study will also explain the concept of unemployment, types, and key factors that cause graduate unemployment, further analyzing its impact on graduates, families and communities in Tragan province, Libya.To achieve the objectives outlined, interviews were conducted on several responsible parties in the Tragan Municipal Council based on the functions and responsibilities held. Next, the interview data obtained were analyzed by comparing these findings with previous studies. The results of this study show that the causes of unemployment and its effects in Tragan, Libya are in line with the results shown by previous studies related to unemployment. The study revealed the main causes of unemployment are the lack of new development projects, and the absence of government role in recruitment, as well as the weakness of the private sector, which is supposed to be a competitor to the public sector and absorb the new entrants to the labor market. The study also shows that the main causes of unemployment in Tragan, Libya are due to the lack of new development projects, and the lack of a government role in hiring, the weakness of the private sector that should be a public sector competitor and the absorption of foreigners into the labor market. As a result, the unemployment implications of these graduates give many complications to graduates, families and the government. Therefore, this study suggests the following solutions: rational planning, development of development programs to accommodate university graduates, strengthening the private sector and supporting small and medium industries. In addition, this study suggests that graduates strive to create their own jobs and do not expect government assistance by developing appropriate projects individually or collectively and obtain appropriate funds to initiate activities appropriate to Islamic financial forms such as through platforms such as Zakat, Mudaraba , effective financing, which serves to revive unprofitable land.